Future supply of boreal forest ecosystem services is driven by management rather than by climate change ... - Triviño, María; Morán-Ordoñez, Alejandra; Eyvindson, Kyle; Blattert, Clemens; Burgas, Daniel; Repo, Anna; Pohjanmies, Tähti; Brotons, Lluís; Snäll, Tord; Mönkkönen, Mikko (Dryad, 2022)
Forests provide a wide variety of ecosystem services (ES) to society. The boreal biome is experiencing the highest rates of warming on the planet and increasing demand for forest products. To foresee how to maximize the adaptation of boreal forests to future warmer conditions and growing demands of forest products, we need a better understanding of the relative importance of forest management and climate change on the supply of ecosystem services. Here, using Finland as a boreal forest case study, we assessed the potential supply of a wide range of ES (timber, bilberry, cowberry, mushrooms, carbon storage, scenic beauty, species habitat availability and deadwood) given seven management regimes and four climate change scenarios. We used the forest simulator SIMO to project forest dynamics for 100 years into the future (2016–2116) and estimate the potential supply of each service using published models. Then, we tested the relative importance of management and climate change as drivers of the future supply of ...